Current status and future perspectives of antibody-drug conjugates in breast cancer therapy - LIN Jialin, WANG Wenna, XU Binghe (Zhongguo aizheng zazhi)
Antibody-drug conjugates (ADCs) represent a breakthrough in precision therapy for breast cancer, offering a unique targeted drug delivery mechanism that enhances tumor selectivity while reducing the nonspecific toxicity associated with conventional chemotherapy. In recent years, the clinical applications of ADCs in breast cancer have expanded significantly, particularly in human epidermal growth factor receptor 2 (HER2)-positive and HER2-low breast cancer, reshaping the therapeutic landscape. Trastuzumab emtanserin (T-DM1) was the first ADC drug to replace lapatinib plus capecitabine as a second-line treatment for HER2-positive breast cancer, while trastuzumab deruxtecan (T-DXd) demonstrated remarkable efficacy in HER2-low breast cancer in the DESTINY-Breast04 trial, becoming the first approved ADC for this patient subgroup. Furthermore, trophoblast cell surface antigen 2 (Trop-2)-targeting ADCs, such as sacituzumab govitecan (SG), have shown promising clinical benefits in patients with triple-negative breast cancer (TNBC) and hormone receptor-positive/HER2-negative breast cancer. Advances in next-generation ADC technologies, including improvements in linker stability, drug-to-antibody ratio (DAR) optimization, and enhanced bystander effects, have further improved the therapeutic efficacy and safety profile of these agents, reinforcing their role in the precision treatment of breast cancer. Although ADCs have demonstrated substantial clinical benefits, they are associated with target- and payload-related toxicities. However, with ongoing advancements in management strategies, their safety profile has been significantly improved. HER2-targeting ADCs present specific adverse events, including interstitial lung disease (ILD) associated with T-DXd, thrombocytopenia, and liver function abnormalities observed with T-DM1, while Trop-2-targeting ADCs such as SG are linked to hematologic toxicity and gastrointestinal side effects. Notably, structural optimizations in next-generation ADCs have led to significant improvements in their safety profile. Early monitoring, individualized dose modifications, and supportive care measures have been shown to effectively reduce the incidence of severe adverse events. Clinical studies indicate that toxicity management strategies for ADCs have matured, with most adverse effects being effectively controlled through optimized treatment regimens and adjunctive supportive care. Thus, in clinical practice, it is essential to consider patient-specific factors, prior treatment history, and comorbidities to devise an optimal ADC treatment strategy that maximizes both efficacy and safety. As ADC technology continues to evolve, breast cancer treatment is expected to become increasingly precise. The development of novel HER2-Trop-2 bispecific ADCs offers new therapeutic options for patients with HER2-low and HER2-negative breast cancer. Additionally, studies investigating the combination of T-DXd with immune checkpoint inhibitors (ICIs), CDK4/6 inhibitors, and poly (ADP-ribose) polymerase (PARP) inhibitors have demonstrated synergistic antitumor effects, further expanding the prospects for precision medicine in breast cancer. This review systematically summarized the latest advancements in ADCs for breast cancer, with a focus on the clinical applications, safety management strategies, and future development of HER2- and Trop-2-targeting ADCs, aiming to provide valuable insights for the future of precision breast cancer treatment.